Uterine prolapse: Should hysterectomy specimens be subjected for histopathological examination? - Rupali Awale; Roma Isaacs; Shavinder Singh; Kavita Mandrelle (Wolters Kluwer Medknow Publications, 2017)
Context: Uterine prolapse accounts for one of the common gynecological problems in India. The excised uterus is not expected to have any pathological finding other than atrophic endometrium and may be an ulcer because of the prolapse. Aims: The aim of this study is to assess the hysterectomy specimen for unsuspected pathology. Subjects and Methods: The study is done over two and half years at a tertiary care hospital. Hysterectomy specimens done with a clinical indication of prolapse were included in the study. Histopathological examination done, findings noted, and data analyzed. Statistical Analysis Used: Descriptive analysis was used in this study. Results: Of the total hysterectomy specimens, 55 (6%) were done for uterovaginal prolapse. Patients age ranged from 32 to 78 years; mean 51.1 ± 11.9 years. Majority (46; 83.6%) of the patients were above 40 years of age, whereas only (9; 16.4%) were < 40 years of age (P < 0.0001) Vaginal hysterectomy was done in most 38 (69.1%) cases as compared to abdominal hysterectomy in 17 (30.9%) cases (P < 0.001). Adnexae were removed in only 3 (5.5%) cases as compared to 52 (94.5%) cases, in which adnexae were preserved (P < 0.001). Chronic cervicitis was seen in 100% of cases. Majority (18:32.7%) of the endometrium was in atrophic phase, secretory in 8 (14.5%), cystic regressive hyperplasia and chronic endometritis in 4 (7.2%) each. Myometrium was unremarkable in 43 (79%) cases, whereas focal adenomyosis in 12 (21%) cases. All the adnexa received were histologically unremarkable. Conclusions: Grossly unremarkable specimens can have unsuspected histopathological lesion which could be potential premalignant or malignant lesions. Therefore, all hysterectomy specimens should be subjected to the histopathological examination for accurate diagnosis and proper categorization of lesions.